ANALISIS MOTIVASI KERJA PEGAWAI PADA BADAN KEPEGAWAIAN DAERAH KABUPATEN MALINAU PROVINSI KALIMANTAN TIMUR - Sedarmayanti, Sedarmayanti (Sekolah Tinggi Ilmu Administrasi Lembaga Administrasi Negara, 2013)
In an organization can not be separated from the human resources available, in addition to other resources. The achievement of an organization's vision, mission certainly not terlepasa of performance generated by existing employees.Therefore, in this case the district Regional Employment Board Malinau a formal organization in the District Government Malinau. Regional Employment Board Malinau certainly has the vision, mission and goals of the organization that must be understood by every employee. For fulfilling their visi, the mission must be supported with a strong work motivation of each employee. Starting from this, the thesis takes the title of